Dr. Kenji Kuwazuru — Deep Plane Facelift — Osaka - Kuwazuru, Kenji (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kenji Kuwazuru, practicing in Osaka, Japan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002967; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; japan; osaka